Prevalence of endocrine and metabolic disorders in subjects with erectile dysfunction: a comparative study - Maseroli, Elisa; Corona, Giovanni; Rastrelli, Giulia; Lotti, Francesco; Cipriani, Sarah; Forti, Gianni; Mannucci, Edoardo; Maggi, Mario (Journal of sexual medicine, 2015)
Alterations of gonadal, thyroid, and pituitary hormones, along with metabolic disorders, might be involved in causing erectile dysfunction (ED). The prevalence of endocrine abnormalities in two different cohorts from the general and the symptomatic populations of Florence was compared. The first group is a general population sample derived from a Florentine spin-off of the European Male Aging Study (EMAS cohort; n = 202); the second group is a series of n = 3,847 patients attending our clinic for ED (UNIFI cohort). Both primary and secondary hypogonadism were more often observed in the UNIFI than in the EMAS cohort (2.8 vs. 0%; P < 0.05 and 18.9 vs. 8%; P < 0.001, respectively). However, only the second association retained statistical significance after adjusting for age. Compensated hypogonadism was more common in the EMAS cohort (4.4 vs. 8.1%; P < 0.05). No statistically significant difference in the prevalence of overt thyroid disorders was observed. Conversely, subclinical hyperthyroidism was more prevalent in the EMAS cohort (2 vs. 4.1%, P < 0.05). No significant difference in the prevalence of hyperprolactinemia was detected, while the prevalence of hypoprolactinemia was significantly higher in the UNIFI than in the EMAS cohort (28.2% vs. 17.8%, P = 0.001), even after the adjustment for age, BMI, and testosterone (P = 0.001). Central obesity (waist ≥102 cm), impaired fasting glucose (IFG), and type 2 diabetes mellitus (T2DM) were more often detected in UNIFI patients (31.7 vs. 22.8%, P < 0.05; 44.5 vs. 33.3%, P < 0.05; 20.1% vs. 1.0%, P < 0.001 in the UNIFI and EMAS cohort, respectively), even after adjusting for age. In contrast, the prevalence of overweight and obesity did not differ between the two groups. T2DM, IFG, central obesity, secondary hypogonadism, and hypoprolactinemia are more frequent in subjects consulting for ED than in the general population of the same geographic area. Our data suggest that these conditions could play a central role in determining consultation for ED.